1953
DOI: 10.1021/ja01102a033
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Some Organophosphorus Compounds Possessing Anticholinesterase Activity1

Abstract: 1379taining group (i.e., the sulfonyl group), as in the change from hippurate ion to benzenesulfonylglycinate, causes a very large decrease in the strength of combination. This large effect may be entirely steric and due to the larger space requirement of two oxygens.In the absence of the carbonyl group, there seems to be some correlation between the combining power of the hapten and the distance between the benzene group and the carboxylate ion. Phenylbutyrate ion, in which the benzene and carboxylate have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…After complete hydrolysis, the mixture was concentrated in vacuum to afford the products ( 3a–l ) in yields of 71–93% in a purity of at least 98%. From among the arylphosphonic acids, 3a, 3c, 3f, 3g , and 3k have been described and partially characterized , 3b and 3h–j were described and characterized only by a melting point , whereas the remaining products 3d, 3e , and 3l are new. Spectral parameters of the known species were compared with those of authentic samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After complete hydrolysis, the mixture was concentrated in vacuum to afford the products ( 3a–l ) in yields of 71–93% in a purity of at least 98%. From among the arylphosphonic acids, 3a, 3c, 3f, 3g , and 3k have been described and partially characterized , 3b and 3h–j were described and characterized only by a melting point , whereas the remaining products 3d, 3e , and 3l are new. Spectral parameters of the known species were compared with those of authentic samples.…”
Section: Resultsmentioning
confidence: 99%
“…(2‐Fluorophenyl)Phosphonic Acid ( 3i ) . Yield: 81%; mp: 144–146°C, mp : 146–149°C; 31 P NMR (DMSO) δ : 7.4; 13 C NMR (DMSO) δ : 115.6 (dd, J 1 = 7.1, J 2 = 22.4, C 3 ), 121.2 (dd, J 1 = 178.7, J 2 = 19.1, C 1 ), 123.8 (dd, J 1 = 12.8, J 2 = 3.3, C 5 ), 133.2 (dd, J 1 = 5.3, J 2 = 5.0, C 4 ), 133.5 (dd, J 1 = 8.3, J 2 = 1.5, C 6 ), 162.4 (d, J = 247.4, C 2 ); 1 H NMR (DMSO) δ : 7.18–7.28 (m, 2H, ArH) 7.52–7.59 (m, 1H, ArH), 7.65–7.75 (m, 1H, ArH); (M + H) + found = 177.0123, C 6 H 7 FO 3 P requires 177.0117.…”
Section: Methodsmentioning
confidence: 99%
“…A possible explanation for the lack of inhibitory activity by 3 and 4 could be that these complexes exist in the basic buffer solution as ionic complexes, which probably interact with the hydrophobic surface of cutinase in a repelling manner, thereby preventing them from entering the active site. Related to this, Freedman et al reported the inhibitory activity of related phenylphosphonic and phenylphosphinic acids toward acetylcholine esterase, for which strong inhibition activities were found in some examples 15. The enzyme has an active site similar to that of cutinase (i.e.…”
Section: Resultsmentioning
confidence: 91%
“…However, they have never been tested for lipases, e.g. cutinase 15. From a synthetic point of view, pincer‐containing phosphonic acids 3 and 4 (Figure 2) are of interest, since the route to their synthesis appeared to be considerably shorter than the synthetic route to phosphonate compounds like 1 and 2 16.…”
Section: Introductionmentioning
confidence: 99%
“…o -Aminophenylphosphonic acid was tested for its anticholesterinase activity [ 27 ] and 2-amino-4-methylphenylphosphonic acid for removing formaldehyde adducts [ 28 ] from RNA and DNA bases. The protected o -aminoarylphosphonates prepared by [1,3]-migration of phosphorus can be deprotected to give o -aminoarylphosphonic acids as shown for three examples (Scheme 8 ).…”
Section: Resultsmentioning
confidence: 99%